2020
DOI: 10.1029/2019jb018001
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control on Megathrust Rupture and Slip Behavior: Insights From the 2016 Mw 7.8 Pedernales Ecuador Earthquake

Abstract: The heterogeneous seafloor topography of the Nazca Plate as it enters the Ecuador subduction zone provides an opportunity to document the influence of seafloor roughness on slip behavior and megathrust rupture. The 2016 Mw 7.8 Pedernales Ecuador earthquake was followed by a rich and active postseismic sequence. An internationally coordinated rapid response effort installed a temporary seismic network to densify coastal stations of the permanent Ecuadorian national seismic network. A combination of 82 onshore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 78 publications
(200 reference statements)
2
18
0
1
Order By: Relevance
“…This is implied by the comparison of the coseismic slip distribution with the aftershock distribution (Figures 1a and 1d), where it is demonstrated that aftershocks cluster around the main slip patch and only very few aftershocks overlap the area of high coseismic slip. This remark is in line with other cases of individual moderate and large earthquakes, where the main asperities that broke during the main shock displayed low aftershock activity (e.g., Ebel & Chambers, 2016;Frank et al, 2017;Kato & Igarashi, 2012;Ross et al, 2017;Soto-Cordero et al, 2020;Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This is implied by the comparison of the coseismic slip distribution with the aftershock distribution (Figures 1a and 1d), where it is demonstrated that aftershocks cluster around the main slip patch and only very few aftershocks overlap the area of high coseismic slip. This remark is in line with other cases of individual moderate and large earthquakes, where the main asperities that broke during the main shock displayed low aftershock activity (e.g., Ebel & Chambers, 2016;Frank et al, 2017;Kato & Igarashi, 2012;Ross et al, 2017;Soto-Cordero et al, 2020;Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…(2019), and Soto‐Cordero et al. (2020) but also at shallower depths (<20 km) in the upper crust as discussed by León‐Ríos et al. (2019) and Hoskins et al.…”
Section: Resultsmentioning
confidence: 83%
“…Quaternary sediments cover these as well as other small formations, forming several basins along the coast such as the Borbon, Manta–Jama, and Manabi basin (see (1), (2), and (3) in Figure 1b). The local tectonic and seismic activity is controlled by major faults that bound these basins (Agurto‐Detzel et al., 2019; Font et al., 2013; León‐Ríos et al., 2019; Luzieux et al., 2006; Reyes & Michaud, 2012; Reynaud et al., 1999; Soto‐Cordero et al., 2020). Reyes and Michaud (2012) updated the coastal geological map for Ecuador extending several faults observed at the surface.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…The large acceleration of aseismic processes in the postseismic stage (Perfettini et al, 2010) then evokes a higher rate of microseismicity in these mostly creeping regions, which allows the clear identification of such separators close to the main shock area during aftershock series. A recent example is the area of the 2016 M w 7.8 Pedernales earthquake, where the main shock that was situated on the deeper part of the megathrust activated three narrow seismicity "fingers" separating largely aseismic regions in the presumably unruptured part of the megathrust (Agurto-Detzel et al, 2019;Soto-Cordero et al, 2020). As in Central Chile, these features can be correlated with incoming seafloor relief.…”
Section: Mogi Doughnuts and The Temporal Evolution Of Seismicity Pattmentioning
confidence: 99%